1992
DOI: 10.1177/014572179201800409
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Diabetes Mellitus and Periodontal Disease

Abstract: The dental profession is acutely aware of oral health problems associated with diabetes mellitus and clinical manifestations indicative of occult forms of the disease. Periodontal disease is common in patients with diabetes, and its effective management in diabetic patients requires cooperation involving the patient, physician, diabetes educator, dentist, and other allied health care providers. While these patients categorically appear more prone to diseases affecting the supporting tissues of the teeth, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
1
17
0
1
Order By: Relevance
“…Inflammatory bone pathologies are often seen in individuals with T1D, including inflammatory arthritis and periodontitis-associated alveolar bone loss, where inflammatory mediators including bacterial components are abundant in these milieus (Hallmon and Mealey, 1992; Lalla et al, 2007; Mealey and Rose, 2008; Ryan et al, 2003; Somers et al, 2009; Teng, 2006). Thus, the effect of LPS on T1D-derived osteoclast function was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory bone pathologies are often seen in individuals with T1D, including inflammatory arthritis and periodontitis-associated alveolar bone loss, where inflammatory mediators including bacterial components are abundant in these milieus (Hallmon and Mealey, 1992; Lalla et al, 2007; Mealey and Rose, 2008; Ryan et al, 2003; Somers et al, 2009; Teng, 2006). Thus, the effect of LPS on T1D-derived osteoclast function was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in such patients there is higher CAL and more severe periodontal diseases. Some studies have shown a higher rate of tooth decay in diabetic patients due to xerostomia and seepage of glucose into Gingival Cervicular Fluid (GCF) [7,24]. An increase in number of lost teeth in diabetic patients with xerostomia might be attributed to tooth mobility due to periodontal diseases and an increase in the incidence of tooth decay in such patients, which is consistent with the results of present study, indicating higher CAL and more lost teeth in patients with xerostomia.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent daily intake of refined carbohydrates may also contribute to a higher incidence of caries among people with diabetes [14]. Effective control of oral disease can be attained systemically through better glycemic control and locally through improved oral hygiene [15, 16]. …”
Section: Introductionmentioning
confidence: 99%